can you find the cube root of a negative number? if so, is it positive or negative? explain your reasoning

Answers

Answer 1
Answer: yes you can and it is negative because if you think about it, the answer to the 3rd power is your original question, so for example,  -8 would equal to the answer times itself 3 times
now ask yourself, does 2 times itself 3 times = to -8
or -2 times itself 3 times = to -8


Related Questions

Why is 0.04 is 1/10 of 0.4
A person sold 100 shares of stock at a loss of 40%. If the selling price for the 100 shares was $3,000, which of the following comes closest to what was paid for the stock?
Five and one half less than 3 times a number
Kirsten tried to evaluate the expression {12 x 2 - 8} x 2. Her work is below.{12 x 2 - 8} x 2Step 1: = {12 x 2} - 16Step 2: = 24 – 16Step 3: = 8In which step did Kirsten first make a mistake?Choose 1 answer:Step 1BStep 2Step 3Kirsten did not make a mistake
You have 80 pieces of fabric to make a wall hanging. Each piece of fabric is a square with a side length of 5 inches. You use as many pieces of fabric as possible to create a square wall hanging.What is the area of the wall hanging? How many pieces of fabric are left over? How many more pieces of fabric would you need to increase the size of the wall hanging?

a petting zoo has 5 lambs 11 rabbits 4 goats and 4 piglets. find the ratio of goats to the total number of animals. write the ratio in the simplest form then explain its meaning

Answers

5 over 19 is the number of goats to animals

Find the remainder when 1 + 2 + 2^2 + 2^3 + ... + 2^100 is divided by 7.Thanks in advance!

Answers

Answer:

3.

Step-by-step explanation:

This is a geometric series so the sum is:

a1 * r^n - 1 / (r - 1)

= 1 * (2^101 -1) / (2-1)

= 2^101 - 1.

Find the remainder when 2^101 is divided by 7:

Note that 101 = 14*7 + 3 so

2^101 = 2^(7*14 + 3) =  2^3  * (2^14)^7 = 8 * (2^14)^7.

By Fermat's Little Theorem  (2^14) ^ 7 = 2^14 mod 7 = 4^7 mod 7.

So 2^101 mod 7 = (8 * 4^7) mod 7

                           = (8 * 4) mod 7

                            = 32 mod 7

                            = 4 = the remainder when 2^101 is divided by 7.

So the remainder when 2^101- 1 is divided by 7 is 4 - 1 = 3..

7(4+5+2)-6(3+5) evaluate the expression

Answers

Answer:

29

Step-by-step explanation:

7(4 + 5 + 2) - 6(3 + 5)

First we need to know what PEMDAS is. It is an acronym that helps remind you what steps to take when evaluating any kind of equation or expression.

  1. P-arentheses
  2. E-xponents
  3. M-ultiplication
  4. D-ivision
  5. A-ddition
  6. S-ubtraction

In PEMDAS, multiplication/division and addition/subtraction are in no particular order-- they are solved from left to right.

Knowing what PEMDAS means, you can start evaluating the expression. Start by solving inside the parentheses, as PEMDAS tells you to do.

Add 4 + 5 + 2 and 3 + 5 inside of the two parentheses in the expression.

7(11) - 6(8)

Since there are no exponents, you can skip this step and move on to multiplying 7 * 11 and 6 * 8.

(77) - (48)

The final process in evaluating this expression is to subtract 48 from 77.

29 is your answer.

Answer:

7(11) -6(8)

77-48=29

Step-by-step explanation:


What is nth term for 0 6 24 54 96?

Answers

Therefore, in the nthterm it would be (n-1)+(18+12^n)=12^n+n+17.

What is the sequence ?

A sequence is a list of objects, typically numbers, in which order matters, repetition is allowed, and the same elements can appear multiple times at different positions in the sequence.

Here given sequence is

0,6,24,54,96,..

Then ,

0+6=6\n6+18=24\n24+(18+12)=54\n54+(18+12+12)=96\n96+(18+12+12+12)=150\n150+(18+12+12+12+12)=216\n216+(18+12+12+12+12+12)=294\n294+(18+12+12+12+12+12+12)=384\n.\n.\n.\n(n-1)+(18+12^n)=12^n+n+17

Hence, in the nthterm it would be (n-1)+(18+12^n)=12^n+n+17.

To know more about the sequence

brainly.com/question/28662470

#SPJ6

I did this via trial and error, so I don't have a good explanation (just good intuition):

6n^(2)

Question in pic, will mark brainliest.

Answers

Answer:

c.  40.

Step-by-step explanation:

Since the small and large triangles are similar we have the equation:

45 / 90 = 6x + 4 / 4x + 56

1 /2 = 6x + 4 / 4x + 56

2(6x + 4)  = 4x + 56

12x + 8 = 4x + 56

8x = 48

x = 6

So the length of the mid segment = 6(6) + 4 = 40.

Answer:

the anwser is A

Step-by-step explanation:

How does the graph change between point A and point B?

Answers

The graph increases between point A and point B